The effect of training the fathers to support their wives on stress and self-efficacy in mothers of premature newborns hospitalized in NICU: a quasi-experimental study - Zahra Hadian Shirazi; Hamed Ghasemloo; Seyyed Mostajab Razavinejad; Nasrin Sharifi; Shahpar Bagheri (BMC Pregnancy and Childbirth, 2022)
Abstract Background The birth of premature newborns and their separation from family due to their hospitalization in the Neonatal Intensive Care Unit (NICU) cause stress in the parents, especially mothers. We conducted this study aimed to evaluate whether training the fathers to support their wives impacts premature newborn mothers’ stress and self-efficacy or not? Methods A quasi-experimental (before-after study) including one experimental and control group was used. Data were collected from Seventy-five parents with newborns hospitalized in NICU (n = 30) in the intervention and (n = 45) in usual care groups. Settings were the NICUs of the two international, educational, specialty, and subspecialty Nemazee and Hafez hospitals of the Shiraz University of Medical Science. Fathers in the intervention group learned how to support their wives and provide care for their premature newborns. The control group received the usual care. Mother’s stress and self-efficacy were measured using validated questionnaires. Results Data analysis showed that the mean scores of mothers’ stress and self-efficacy from pre-intervention to post-intervention were significantly decreased and increased respectively in the intervention group (p <0.001). At the same time, there was no significant difference in the control group. Conclusion When fathers are trained to support their wives and do so, it relieves the stress and improves the mothers’ self-efficacy, and has a direct effect on providing care to their premature newborns. Therefore, it is recommended that measures should be taken so that the fathers be present, participate in providing care, and support their wives and newborns in NICU. Trial registration IRCT20171130037691N1 .